2016
DOI: 10.1186/s12886-016-0373-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bradykinin on TGF-β1-induced retinal pigment epithelial cell proliferation and extracellular matrix secretion

Abstract: BackgroundTo evaluate the effect of bradykinin (BK) on TGF-β1-induced retinal pigment epithelial (RPE) cell proliferation and extracellular matrix secretion and to elucidate the relationship between BK and the Erk/Akt signaling pathway.MethodsThe effects of BK on TGF-β1-induced RPE cell proliferation were examined via CCK-8 assay. Cell culture supernatant collagen I concentrations were measured via ELISA. Fibronectin (Fn), matrix metalloproteinase-2 (MMP-2) and MMP-9 mRNA and protein expression levels were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These effects were reversed by NO synthase inhibitor L-NAME, vasoinhibins, and N-acetyl cysteine (Arredondo Zamarripa et al 2014). Bradykinin could also inhibit TGF-β1-stimulated ARPE-19 cell proliferation, collagen I, fibronectin, and MMP-2 secretion as well as Akt phosphorylation via activating bradykinin receptor 2 (Cai et al 2016). In normal rats, bradykinin-induced vasodilatation was involved in intracellular Ca2 + mobilization and products of the cyclooxygenase-2 (COX-2) pathway, but in STZ-diabetic rats, the vasodilatation in response to des-Arg9-bradykinin was involved in both calcium influx and intracellular calcium mobilization, which was blocked by GdCl 3 , 2,5-di-tbutylhydroquinone, and cADP ribose (Abdouh et al 2003).…”
Section: Hyperosmolar Stress and Diabetic Retinopathymentioning
confidence: 94%
“…These effects were reversed by NO synthase inhibitor L-NAME, vasoinhibins, and N-acetyl cysteine (Arredondo Zamarripa et al 2014). Bradykinin could also inhibit TGF-β1-stimulated ARPE-19 cell proliferation, collagen I, fibronectin, and MMP-2 secretion as well as Akt phosphorylation via activating bradykinin receptor 2 (Cai et al 2016). In normal rats, bradykinin-induced vasodilatation was involved in intracellular Ca2 + mobilization and products of the cyclooxygenase-2 (COX-2) pathway, but in STZ-diabetic rats, the vasodilatation in response to des-Arg9-bradykinin was involved in both calcium influx and intracellular calcium mobilization, which was blocked by GdCl 3 , 2,5-di-tbutylhydroquinone, and cADP ribose (Abdouh et al 2003).…”
Section: Hyperosmolar Stress and Diabetic Retinopathymentioning
confidence: 94%
“…Elevated TGF-β levels have been reported in the subretinal fluids, vitreous and epiretinal membranes of patients with PVR (27)(28)(29)(30). TGF-β serves a vital role in PVR formation since it regulates cell proliferation, enhances ECM protein synthesis and induces ECM deposition (23,31). It has been previously demonstrated that the inhibition of TGF-β expression may prevent PVR progression (32).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that multiple growth factors and cytokines are involved in the vitreous body of PVR patients, including tumor necrosis factor-α, interleukin-(IL-) 6, transforming growth factor-beta (TGF-β) and epidermal growth factor (EGF) 4. In our previous studies, TGF-β1 was found to have an essential role in EMT in RPE cell lines (ARPE-19) 5,6. TGF-β1-induced EMT triggers epithelial cells to alter their epithelial phenotype to one with mesenchymal characteristics, and the proliferation, migration, and collagen generation of TGF-β1-induced RPE cells are enhanced, accelerating EMT progression.…”
Section: Introductionmentioning
confidence: 94%